If $ {\log _b}a.{\log _c}a + {\log _a}b.{\log _c}b + {\log _a}c.{\log _b}c = 3 $ (where a, b, c are different positive real numbers ≠ 1) then find the value of $ abc $ .
Answer
Verified
463.5k+ views
Hint: A logarithm, of a base b, is the power to which the base needs to be raised to yield a given number. We know that $ {\log _b}a = \dfrac{{\log a}}{{\log b}} $ , so first convert the given logarithmic terms with bases to this form using this conversion. And then solve the remaining solution referring to the below mentioned formula.
Formulas used:
$ {\log _b}a = \dfrac{{\log a}}{{\log b}} $
If $ x + y + z = 0 $ , then $ {x^3} + {y^3} + {z^3} = 3xyz $ and vice-versa.
Complete step-by-step answer:
We are given a logarithmic equation $ {\log _b}a.{\log _c}a + {\log _a}b.{\log _c}b + {\log _a}c.{\log _b}c = 3 $ where a, b, c are different positive real numbers ≠ 1.
We have to find the value of $ abc $ .
As we already know that $ {\log _b}a = \dfrac{{\log a}}{{\log b}} $ .
Therefore, Using the above conversion we are converting the logarithmic terms present in the given equation into this fractional form.
$ {\log _c}a = \dfrac{{\log a}}{{\log c}} $
$ {\log _a}b = \dfrac{{\log b}}{{\log a}} $
$ {\log _c}b = \dfrac{{\log b}}{{\log c}} $
$ {\log _a}c = \dfrac{{\log c}}{{\log a}} $
$ {\log _b}c = \dfrac{{\log c}}{{\log b}} $
On substituting all the obtained fractional terms in $ {\log _b}a.{\log _c}a + {\log _a}b.{\log _c}b + {\log _a}c.{\log _b}c = 3 $ , we get
$ \left( {\dfrac{{\log a}}{{\log b}} \times \dfrac{{\log a}}{{\log c}}} \right) + \left( {\dfrac{{\log b}}{{\log a}} \times \dfrac{{\log b}}{{\log c}}} \right) + \left( {\dfrac{{\log c}}{{\log a}} \times \dfrac{{\log c}}{{\log b}}} \right) = 3 $
$ \Rightarrow \dfrac{{{{\left( {\log a} \right)}^2}}}{{\log b.\log c}} + \dfrac{{{{\left( {\log b} \right)}^2}}}{{\log a.\log c}} + \dfrac{{{{\left( {\log c} \right)}^2}}}{{\log a.\log b}} = 3 $
Take out the LCM and convert the above left hand side into a single fraction, the LCM is $ \log a.\log b.\log c $
$ \Rightarrow \dfrac{{\log a \times {{\left( {\log a} \right)}^2} + \log b \times {{\left( {\log b} \right)}^2} + \log c \times {{\left( {\log c} \right)}^2}}}{{\log a.\log b.\log c}} = 3 $
$ \Rightarrow \dfrac{{{{\left( {\log a} \right)}^3} + {{\left( {\log b} \right)}^3} + {{\left( {\log c} \right)}^3}}}{{\log a.\log b.\log c}} = 3 $
On cross multiplication, we get
$ \Rightarrow {\left( {\log a} \right)^3} + {\left( {\log b} \right)^3} + {\left( {\log c} \right)^3} = 3 \times \left( {\log a.\log b.\log c} \right) = 3\log a.\log b.\log c $
As we can see, the above equation is in the form of $ {x^3} + {y^3} + {z^3} = 3xyz $ , where x is $ \log a $ , y is $ \log b $ and z is $ \log c $
Therefore, $ x + y + z $ must be equal to zero which means $ \log a + \log b + \log c = 0 $
We know that $ \log a + \log b $ is equal to $ \log ab $
Therefore, $ \log a + \log b + \log c = \log abc $
$ \log abc = 0 $
Sending the logarithm to the right hand side (as $ \log abc $ is a common logarithm it will have a base 10)
$ abc = {10^0} = 1 $ (Anything to the power zero is equal to 1)
Therefore, the value of $ abc $ is 1.
So, the correct answer is “1”.
Note: We know that $ {\log _b}a = \dfrac{{\log a}}{{\log b}} $ , which can also be written as $ \dfrac{1}{{\left( {\dfrac{{\log b}}{{\log a}}} \right)}} = \dfrac{1}{{{{\log }_a}b}} $ . And while finding the value of $ {\log _b}a $ , confirm that b is always greater than zero and never equal 1; a must be a positive real number. If $ {\log _b}a = k $ , then $ a = {b^k} $
Formulas used:
$ {\log _b}a = \dfrac{{\log a}}{{\log b}} $
If $ x + y + z = 0 $ , then $ {x^3} + {y^3} + {z^3} = 3xyz $ and vice-versa.
Complete step-by-step answer:
We are given a logarithmic equation $ {\log _b}a.{\log _c}a + {\log _a}b.{\log _c}b + {\log _a}c.{\log _b}c = 3 $ where a, b, c are different positive real numbers ≠ 1.
We have to find the value of $ abc $ .
As we already know that $ {\log _b}a = \dfrac{{\log a}}{{\log b}} $ .
Therefore, Using the above conversion we are converting the logarithmic terms present in the given equation into this fractional form.
$ {\log _c}a = \dfrac{{\log a}}{{\log c}} $
$ {\log _a}b = \dfrac{{\log b}}{{\log a}} $
$ {\log _c}b = \dfrac{{\log b}}{{\log c}} $
$ {\log _a}c = \dfrac{{\log c}}{{\log a}} $
$ {\log _b}c = \dfrac{{\log c}}{{\log b}} $
On substituting all the obtained fractional terms in $ {\log _b}a.{\log _c}a + {\log _a}b.{\log _c}b + {\log _a}c.{\log _b}c = 3 $ , we get
$ \left( {\dfrac{{\log a}}{{\log b}} \times \dfrac{{\log a}}{{\log c}}} \right) + \left( {\dfrac{{\log b}}{{\log a}} \times \dfrac{{\log b}}{{\log c}}} \right) + \left( {\dfrac{{\log c}}{{\log a}} \times \dfrac{{\log c}}{{\log b}}} \right) = 3 $
$ \Rightarrow \dfrac{{{{\left( {\log a} \right)}^2}}}{{\log b.\log c}} + \dfrac{{{{\left( {\log b} \right)}^2}}}{{\log a.\log c}} + \dfrac{{{{\left( {\log c} \right)}^2}}}{{\log a.\log b}} = 3 $
Take out the LCM and convert the above left hand side into a single fraction, the LCM is $ \log a.\log b.\log c $
$ \Rightarrow \dfrac{{\log a \times {{\left( {\log a} \right)}^2} + \log b \times {{\left( {\log b} \right)}^2} + \log c \times {{\left( {\log c} \right)}^2}}}{{\log a.\log b.\log c}} = 3 $
$ \Rightarrow \dfrac{{{{\left( {\log a} \right)}^3} + {{\left( {\log b} \right)}^3} + {{\left( {\log c} \right)}^3}}}{{\log a.\log b.\log c}} = 3 $
On cross multiplication, we get
$ \Rightarrow {\left( {\log a} \right)^3} + {\left( {\log b} \right)^3} + {\left( {\log c} \right)^3} = 3 \times \left( {\log a.\log b.\log c} \right) = 3\log a.\log b.\log c $
As we can see, the above equation is in the form of $ {x^3} + {y^3} + {z^3} = 3xyz $ , where x is $ \log a $ , y is $ \log b $ and z is $ \log c $
Therefore, $ x + y + z $ must be equal to zero which means $ \log a + \log b + \log c = 0 $
We know that $ \log a + \log b $ is equal to $ \log ab $
Therefore, $ \log a + \log b + \log c = \log abc $
$ \log abc = 0 $
Sending the logarithm to the right hand side (as $ \log abc $ is a common logarithm it will have a base 10)
$ abc = {10^0} = 1 $ (Anything to the power zero is equal to 1)
Therefore, the value of $ abc $ is 1.
So, the correct answer is “1”.
Note: We know that $ {\log _b}a = \dfrac{{\log a}}{{\log b}} $ , which can also be written as $ \dfrac{1}{{\left( {\dfrac{{\log b}}{{\log a}}} \right)}} = \dfrac{1}{{{{\log }_a}b}} $ . And while finding the value of $ {\log _b}a $ , confirm that b is always greater than zero and never equal 1; a must be a positive real number. If $ {\log _b}a = k $ , then $ a = {b^k} $
Recently Updated Pages
Master Class 11 Accountancy: Engaging Questions & Answers for Success
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Trending doubts
10 examples of friction in our daily life
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE
Define least count of vernier callipers How do you class 11 physics CBSE